Digital literacy for Madrasah Reachers: Strategies for Navigating Misinformation in Islamic - Ahmad Yani (Yayasan Adra Karima Hubbi, 2025)
Background. The proliferation of digital information has presented unprecedented challenges for madrasah teachers, who are pivotal in shaping the religious understanding of Muslim generations. The unchecked spread of misinformation and disinformation related to Islamic teachings poses a significant threat to religious moderation and social harmony. Purpose. This study aims to identify and analyze the challenges madrasah teachers face in navigating online misinformation and to formulate effective, pedagogically sound strategies to enhance their digital literacy skills for this specific purpose. Method. Employing a qualitative research design, this study utilized in-depth interviews and focus group discussions with 30 madrasah teachers across different educational levels. A thematic analysis approach was used to systematically code and interpret the collected data, allowing for a nuanced understanding of the participants’ experiences and needs. Results. The findings reveal that while teachers are aware of the dangers of online misinformation, they often lack the critical skills and resources to effectively vet digital Islamic content. Key challenges include the inability to distinguish between credible and dubious online sources, the emotional appeal of sensationalist religious content, and a lack of formal training. Conclusion. Enhancing the digital literacy of madrasah teachers is not merely a technical imperative but a pedagogical necessity to safeguard authentic Islamic education. A proactive, continuous, and context-specific approach is crucial for empowering teachers to become resilient navigators of the digital landscape and effective guides for their students against religious misinformation.